Preparation method of aluminum alloy composite board
The preparation of aluminum alloy composite sheets through stirring and smelting and multiple treatment processes solves the problems of complex and insufficient performance in the existing process, and achieves the effects of high strength, high toughness and simplified processes.
Patent Information
- Application Number
- CN202411888696.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing aluminum alloy composite sheet preparation process has problems such as complex process, difficulty in operation, requiring subsequent heat treatment, and limited material performance strength and toughness.
Al-Si-Mg and Al-Zr alloy melts were prepared by stirring and melting, and casting, homogenization, solid solution treatment, aging treatment, deep cold treatment and cold rolling. Subsequently, powder stacking and accumulated stacking welding were carried out to prepare aluminum alloy composite sheets.
The high strength, high toughness and excellent comprehensive mechanical properties of aluminum alloy composite sheets are achieved, which reduces subsequent heat treatment steps, simplifies the process flow, and reduces production costs.
Smart Images

Figure CN119588937A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and particularly relates to a method for preparing an aluminum alloy composite plate. Background Art
[0002] Aluminum is the most abundant metal element in the earth's crust. After alloying, it has a wide range of applications in practical applications. Aluminum-silicon alloys based on aluminum have good strength, hardness, wear resistance, corrosion resistance and conductivity. They are often used to manufacture engine parts, cylinder heads and aluminum core strands in the fields of automobile manufacturing, electrical engineering and mechanical manufacturing. The prepared aluminum core strands are used for transmission lines, manufacturing high-performance bearings, gears and hydraulic components, etc. Aluminum-zirconium alloys have good high temperature resistance, fatigue life and corrosion resistance. They have good application scenarios in aerospace, shipbuilding and chemical industries, and are often used to manufacture aircraft structures, hull structures, chemical equipment and pipelines. At present, the preparation of aluminum alloys will affect the properties of the material due to the different addition amounts of alloying elements. Too high an addition of alloying elements will reduce the thermal stability and processability of the material and increase its brittleness; too low an alloying element content will make it difficult to achieve the expected use effect. Aluminum silicon and aluminum zirconium alloys have different properties and advantages. Through deep cryogenic treatment, the grain size of aluminum alloy can be refined, so that the strength and plasticity of the material can be improved. Accumulative roll-to-roll welding can combine plates with different alloy elements to ensure that the composite plates achieve certain complementary properties. However, too high zirconium content in aluminum zirconium alloy will cause edge cracking during rolling, and the metallurgical interface of different plates after composite rolling is not tightly bonded, the actual process is cumbersome, the cost is high, and the performance of the roll-to-roll material is low, which needs to be solved urgently.
[0003] Chinese patent CN117444536A discloses a composite forming method for a coarse-grained and fine-grained layered distribution structure aluminum alloy. With the assistance of stir friction refinement treatment, ultrasonic additive manufacturing technology is used to complete high-quality rapid consolidation forming of fine-grained aluminum foil and coarse-grained aluminum foil at room temperature or low temperature conditions, thereby obtaining a heterogeneous aluminum alloy formed by alternating fine-grained aluminum layers and coarse-grained aluminum layers with fine-grained aluminum layers on the upper and lower surfaces.
[0004] Chinese patent CN113290048A discloses an aluminum / magnesium / aluminum alloy composite material and a preparation process thereof, comprising the following steps: S1, material design, wherein the materials include lightweight materials, corrosion-resistant materials and high-plasticity materials, and the design principle is that the surface of the corrosion-resistant material is used as the outer surface of the composite material, the lightweight material accounts for as large a proportion as possible while ensuring the strength of the composite material, and the high-plasticity material is designed in the position with high plasticity requirements; S2, material preparation, cleaning the surface of the material to be composited to ensure that there is no oxide or oil on the surface of the material; S3, after laminating the surfaces of the materials to be composited, simply composite the whole; S4, preheating in a furnace; S5, performing multiple hot rolling composites until the material reaches the target thickness; S6, performing thermal diffusion annealing after rolling is completed to prepare a lightweight, high-plasticity aluminum / magnesium / aluminum alloy composite material.
[0005] Chinese patent CN114000182A discloses a method for preparing a metal magnesium-copper-graphene layered composite material, wherein a plurality of magnesium sheets are pretreated, graphene is electrophoretically deposited on the pretreated magnesium sheets under the action of an external electric field, copper powder is mechanically coated to obtain magnesium sheets with circular holes and graphene-copper coatings, which are fixedly stacked and then wrapped, and multiple cumulative hot rolling and annealing treatments are performed to obtain a layered magnesium-based composite sheet reinforced with graphene and copper.
[0006] Among the above patents, CN117444536A uses ultrasonic additive manufacturing technology to prepare layered heterogeneous alloy plates through stir friction welding, CN113290048A uses stamping and hot rolling of composite plates to prepare magnesium / aluminum alloy composite materials, and CN114000182A uses a coating and overlapping rolling method; all three have obtained composite plates with tight metallurgical bonding surfaces and excellent performance, but the equipment used in CN117444536A is expensive, and the additive manufacturing technology needs to control the influence of residual stress on the plate. CN114000182A and CN113290048A perform heat treatment processes after the plate is processed and formed, which reduces the comprehensive mechanical properties of the material. The processing process requires a high level of technology, which will increase production costs and easily cause waste of human and material resources.
[0007] The above patents have the problems of complex process, difficult operation and need for subsequent heat treatment, and the comprehensive mechanical properties and strength of the prepared plates are relatively limited. Summary of the invention
[0008] The object of the present invention is to provide a method for preparing an aluminum alloy composite plate material, wherein the prepared aluminum alloy composite plate material has excellent mechanical properties, high tensile strength and high overall hardness.
[0009] The technical solution adopted by the present invention to solve its technical problem is: The method for preparing the aluminum alloy composite plate of the present invention comprises the following steps: (1) Pure Al, pure Si and pure Mg are stirred and melted, and then kept warm and allowed to stand to prepare an Al-Si-Mg alloy melt; pure Al and Al-Zr master alloy are stirred and melted, and then kept warm and allowed to stand to prepare an Al-Zr alloy melt, and then cast to obtain Al-Si-Mg ingots and Al-Zr ingots respectively; (2) The Al-Si-Mg ingot and the Al-Zr ingot are homogenized, and then subjected to solution treatment and aging treatment to obtain Al-Si-Mg alloy specimens and Al-Zr alloy specimens, and the Al-Si-Mg alloy specimens and the Al-Zr alloy specimens are cut, and then subjected to cryogenic treatment and cold rolling to obtain Al-Si-Mg rolled specimen plates and Al-Zr rolled specimen plates; (3) The Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate are pretreated, powder stacking is performed between the layers of the pretreated Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate, and then bonding, preheating and cumulative lamination welding are performed to obtain an aluminum alloy composite plate.
[0010] in: In the step (1), the smelting temperature is 750-790°C, the casting temperature is 220-250°C, the insulation temperature is 750-790°C, and the insulation time is 20-40 minutes.
[0011] In the step (2), the temperature of the homogenization treatment is 515-525°C, the time of the homogenization treatment is 1.9-2.1h, the temperature of the solution treatment is 525-535°C, the time of the solution treatment is 0.9-1.1h; the temperature of the aging treatment is 238-242°C, the time of the aging treatment is 15.8-16.2h.
[0012] In the step (2), the Al-Si-Mg alloy sample and the Al-Zr alloy sample are cut to a width ratio of 5-8:3-6, a length ratio of 1:1-1.5, and a thickness ratio of 1:1-1.5.
[0013] In the step (2), the medium for cryogenic treatment is liquid nitrogen, the time for cryogenic treatment is 4-10 hours, the reduction of cold rolling is 84-95%, the number of cold rolling passes is 5-8 times, and the thickness of the Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate are both 1.3-1.7 mm.
[0014] In the step (3), the mass percentages of the elements in the aluminum alloy composite plate are Si: 4.0-5.0%, Mg: 0.2-0.8%, Zr: 0.2-1.0%, and the rest is Al.
[0015] The pretreatment in step (3) includes removing edge cracks, surface cleaning, polishing and grinding.
[0016] In the step (3), the powder stacking is to alternately and evenly stack the ultrafine Al powder with a particle size of 1-2µm and the medium Al powder with a particle size of 40-60µm between the layers of adjacent Al-Si-Mg rolled sample plates and Al-Zr rolled sample plates and compact them. The stacking area is the same as the plate surface area of the Al-Zr rolled sample plate. After stacking and compaction, the total thickness of the stacked powder is 200-500µm. The bonding is to place the Al-Zr rolled sample plate between two layers of Al-Si-Mg rolled sample plates. The preheating temperature is 545-555°C and the preheating time is 1-2min.
[0017] In the step (3), the cumulative roll-to-roll welding is performed by alternating hot rolling and cold rolling, the total reduction of the roll-to-roll is 50-90%, and the number of roll-to-roll is 3-6 times.
[0018] The stack rolling is performed twice, the first rolling is hot rolling, and the second rolling is cold rolling; the stack rolling is performed by liquid nitrogen cooling for 4-10 hours immediately after hot rolling, and cold rolling is performed immediately after taking out.
[0019] The present invention mixes Si, Mg and Al and mixes Zr and Al to form two alloy melts. After casting, the alloy melts are subjected to homogenization treatment, solution treatment and aging treatment to obtain alloy samples. In the process of forming the alloy sample, a second phase is precipitated. Subsequently, deep cryogenic treatment, cold rolling and galvanizing are performed to further refine the microstructure grains. In the galvanizing process, coarse grains and fine grains are introduced so that the two grains are combined with each other to form a double-peak structure, which further improves the toughness of the material. No annealing treatment is performed, which can reduce the influence of subsequent heat treatment on the performance of the plate, and ensure the dislocation strengthening effect of the aluminum alloy composite plate after galvanizing. During the lamination rolling, the width of the sample plates rolled on both sides is greater than that of the sample plates rolled in the middle. Before lamination rolling, the ultrafine Al powder and the medium Al powder are alternately stacked in layers between the plates and preliminarily compacted. During lamination rolling under high temperature and high pressure, the powder is melted and welded with the plates. The coarse and fine crystals in the plates are squeezed, so that the position distribution changes, which is conducive to the rapid generation of a double-peak structure, thereby improving the stiffness and strength of the plates. The excess parts of the plates on both sides are fitted under pressure, which can prevent the middle powder from diffusing in the direction perpendicular to the rolling, making it easier for the medium Al powder to form and maintain fibrous coarse crystals, and the ultrafine Al powder forms ultrafine crystals distributed around the coarse crystals. They work together with the fine crystals in the plates to improve the strength and toughness. The two passes before and after the cumulative lamination rolling adopt the method of alternating hot rolling and cold rolling, which has a good retention of the dislocation density of the lamination plate, reduces the porosity of the tissue formed by the powder, and further improves the performance of the plate.
[0020] Compared with the prior art, the present invention has significant advantages: The invention makes the performance of the alloy composite plate finally prepared more excellent, reduces the operation of subsequent processing and is suitable for industrial production; the invention has the advantages that the alloy sample is subjected to solution treatment and aging treatment before cold rolling, and no heat treatment is required after cold rolling, which can avoid the influence of subsequent heat treatment on the performance of the plate, and the precipitated dispersed second phase Mg 2 Si is evenly dispersed on the grain boundaries, which can hinder the growth of grains. Small grains can more effectively reduce stress concentration and crack generation, thereby improving the processing and forming capabilities of materials. Cryogenic treatment can improve the processing performance of the plate, optimize the strengthening of dislocations and the grain refinement of different plates, and different types of plates will produce equiaxed fine grains with different grain sizes after rolling. By making the width of the Al-Si-Mg rolling sample plates on both sides larger than the width of the Al-Zr rolling sample plates, the movement of the powder in the middle stacking layer of the plate is restricted during the stacking, so that the Al powder with different particle sizes stacked between the plates forms a double peak structure of fibrous coarse crystals and ultrafine crystals along the rolling direction. The stacking method of alternating different powder stacking and hot and cold rolling realizes the metallurgical bonding of plates with different alloy elements. After powder stacking, hot rolling ensures that the bonding surface is tightly bonded, producing a bimodal structure. Fine grains can maintain the strength of the plate unchanged, while coarse grains can improve the toughness of the plate. The mixture of coarse grains and fine grains can produce stress-strain gradients to improve the work hardening rate; cold rolling ensures that the Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate further form equiaxed fine grains with different particle sizes, and compacts the powder layer to reduce the porosity. The organizational structure at the metallurgical bonding surface of the cumulative stacking is a continuous gradient-layered-bimodal heterogeneous structure with high strength and toughness.
[0021] In addition, after the different plates are rolled together, a large amount of element addition can be maintained. The form of silicon in the aluminum alloy composite plate changes from dendritic granular silicon to spherical eutectic silicon. 3 Zr is crushed, further ensuring the uniform distribution of the internal structure of the plate. The aluminum alloy composite plate prepared by the present invention is an alloy composite plate with relatively excellent toughness and strength, certain complementary characteristics, simple and efficient rolling process, and excellent comprehensive mechanical properties and physical properties can be obtained without subsequent heat treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the cross-sectional structure of the Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate before the cladding rolling in Example 1; Figure 2 It is a schematic diagram of the cross-sectional structure of the metallurgical bonding surface of the cumulative roll bonding in Example 1; In the figure: 1. Al-Si-Mg rolled sample plate; 2. Al-Zr rolled sample plate; 3. Medium Al powder; 4. Ultrafine Al powder; 5. Fibrous coarse crystals; 6. Equiaxed ultrafine crystals; 7. Al-Si-Mg equiaxed fine crystals; 8. Al-Zr equiaxed fine crystals. DETAILED DESCRIPTION
[0023] The present invention is further described below with reference to the embodiments.
[0024] Example 1 The elements in the aluminum alloy composite plate are calculated by mass percentage, and the element composition is Si 4.0%, Mg 0.4%, Zr 0.5%, and the rest is Al.
[0025] The method for preparing an aluminum alloy composite plate comprises the following steps: (1) Calculating the required amounts of Si, Mg and Zr in proportion, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 760°C to melt, adding pure Si and pure Mg in turn, stirring and melting at 760°C, and then keeping it at 760°C for 40 minutes to prepare an Al-Si-Mg alloy melt, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 760°C to melt, adding an Al-Zr intermediate alloy, stirring and melting at 760°C, and then keeping it at 760°C for 40 minutes to prepare an Al-Zr alloy melt, and then sending them into a 220°C mold for casting to obtain an Al-Si-Mg ingot and an Al-Zr ingot; (2) The Al-Si-Mg ingot and the Al-Zr ingot were homogenized at 520°C for 2 h, furnace cooled for 24 h and then air cooled, then solution treated at 530°C for 1 h, and then aged at 240°C for 15 h to obtain Al-Si-Mg alloy specimens and Al-Zr alloy specimens. The Al-Si-Mg alloy specimens and the Al-Zr alloy specimens were cut to a width ratio of 6:5, a length ratio and a thickness ratio of 1:1, and then placed in liquid nitrogen for deep cryogenic treatment for 8 h and then cold rolled. The cold rolling reduction was 90% and the rolling passes were 7 times to obtain Al-Si-Mg rolled specimen plates and Al-Zr rolled specimen plates. The thickness of the Al-Si-Mg rolled specimen plates and the Al-Zr rolled specimen plates were both 1.5 mm. (3) The Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate were pre-treated by removing edge cracks, surface cleaning, polishing and grinding. Then, the Al-Zr rolled sample plate was placed between the two Al-Si-Mg rolled sample plates. A mold that matched the size of the Al-Zr rolled sample plate was placed on the lower Al-Si-Mg rolled sample plate, and 3 layers of ultra-fine Al powder with a particle size of 1 µm and 3 layers of medium Al powder with a particle size of 40 µm were alternately stacked through a screen. The powders were compacted, and the Al-Zr rolled sample plate was placed in the mold for bonding. Then, 3 layers of ultra-fine Al powder with a particle size of 1 µm and 3 layers of medium Al powder with a particle size of 40 µm were alternately stacked through a screen. The powders were compacted and the mold was removed. Then, the upper Al-Si-Mg rolled sample plate was placed on the compacted Al powder for bonding. The total thickness of the stacked powder after stacking and compaction was 200 µm. The structure after bonding was as shown in the figure. Figure 1 As shown, it is preheated at a temperature of 550°C for 2 minutes, followed by alternating hot rolling and cold rolling cumulative rolling welding, with a total rolling reduction of 50%, 5 times of rolling, the first pass of cumulative rolling with a hot rolling reduction of 25%, and then immediately cooled with liquid nitrogen for 6 hours, and immediately after being taken out, the second pass of cold rolling is performed with a reduction of 25%, forming an aluminum alloy composite plate with an Al-Si-Mg / Al-Zr / Al-Si-Mg structure. The specific structure is shown in Figure 2 shown.
[0026] Example 2 The elements in the aluminum alloy composite plate are calculated by mass percentage, and its element composition is Si 5.0%, Mg 0.8%, Zr 1.0%, and the rest is Al.
[0027] The method for preparing an aluminum alloy composite plate comprises the following steps: (1) Calculating the required amounts of Si, Mg and Zr in proportion, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 790°C to melt, adding pure Si and pure Mg in turn, stirring and melting at 790°C, and then keeping it at 790°C for 20 minutes to prepare an Al-Si-Mg alloy melt, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 790°C to melt, adding an Al-Zr intermediate alloy, stirring and melting at 790°C, and then keeping it at 790°C for 20 minutes to prepare an Al-Zr alloy melt, and then sending them into a 250°C mold for casting to obtain an Al-Si-Mg ingot and an Al-Zr ingot respectively; (2) The Al-Si-Mg ingot and the Al-Zr ingot were homogenized at 525°C for 2.1 h, cooled in the furnace for 24 h and then air-cooled, then solution treated at 530°C for 1.1 h, and then aged at 242°C for 16.2 h to obtain Al-Si-Mg alloy specimens and Al-Zr alloy specimens. The Al-Si-Mg alloy specimens and the Al-Zr alloy specimens were cut to a width ratio of 8:6, a length ratio and a thickness ratio of 1:1.5, and then placed in liquid nitrogen for deep cryogenic treatment for 6 h and then cold rolled. The cold rolling reduction was 90% and the rolling passes were 8 times to obtain Al-Si-Mg rolled specimen plates and Al-Zr rolled specimen plates. The thickness of the Al-Si-Mg rolled specimen plates and the Al-Zr rolled specimen plates were both 1.7 mm. (3) The Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate were pre-treated by removing edge cracks, surface cleaning, polishing and grinding. Then, the Al-Zr rolled sample plate was placed between the two Al-Si-Mg rolled sample plates. A mold that matched the size of the Al-Zr rolled sample plate was placed on the lower Al-Si-Mg rolled sample plate, and three layers of ultra-fine Al powder with a particle size of 2 µm and three layers of medium Al powder with a particle size of 60 µm were alternately stacked through a screen. The powders were compacted, and the Al-Zr rolled sample plate was placed in the mold and laminated. Then, three layers of ultra-fine Al powder with a particle size of 1 µm and three layers of medium Al powder with a particle size of 40 µm medium Al powder is compacted and removed from the mold, and then the upper Al-Si-Mg rolled sample plate is placed on the compacted Al powder for bonding. The total thickness of the stacked powder after piling and compaction is 500µm, and then preheating is performed at a temperature of 555℃ for 2min, followed by alternating hot rolling and cold rolling cumulative rolling welding, with a total rolling reduction of 90%, and 6 rollings. The first hot rolling reduction of the cumulative rolling is 60%, and then it is immediately cooled with liquid nitrogen for 10h. After taking out, the second cold rolling is immediately performed with a reduction of 30% to form an aluminum alloy composite plate with Al-Si-Mg / Al-Zr / Al-Si-Mg structure.
[0028] Example 3 The elements in the aluminum alloy composite plate are calculated by mass percentage, and its element composition is Si 4.0%, Mg 0.2%, Zr 1.0%, and the rest is Al.
[0029] The method for preparing an aluminum alloy composite plate comprises the following steps: (1) Calculating the required amounts of Si, Mg and Zr in proportion, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 750°C to melt, adding pure Si and pure Mg in turn, stirring and melting at 750°C, and then keeping the mixture at 750°C for 40 min to prepare an Al-Si-Mg alloy melt, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 750°C to melt, adding an Al-Zr intermediate alloy, stirring and melting at 750°C, and then keeping the mixture at 750°C for 40 min to prepare an Al-Zr alloy melt, and then feeding them into a mold at 250°C for casting to obtain an Al-Si-Mg ingot and an Al-Zr ingot respectively; (2) The Al-Si-Mg ingot and the Al-Zr ingot were homogenized at 515°C for 2 h, cooled in the furnace for 24 h and then air-cooled, then solution treated at 525°C for 0.9 h, and then aged at 238°C for 15.8 h to obtain Al-Si-Mg alloy specimens and Al-Zr alloy specimens. The Al-Si-Mg alloy specimens and the Al-Zr alloy specimens were cut to a width ratio of 6:5, a length ratio and a thickness ratio of 1:1, and then placed in liquid nitrogen for deep cryogenic treatment for 4 h and then cold rolled. The cold rolling reduction was 84% and the rolling passes were 8 times to obtain Al-Si-Mg rolled specimen plates and Al-Zr rolled specimen plates. The thickness of the Al-Si-Mg rolled specimen plates and the Al-Zr rolled specimen plates were both 1.3 mm. (3) The Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate were pre-treated by removing edge cracks, surface cleaning, polishing and grinding. Then, the Al-Zr rolled sample plate was placed between the two Al-Si-Mg rolled sample plates. A mold that matched the size of the Al-Zr rolled sample plate was placed on the lower Al-Si-Mg rolled sample plate, and three layers of ultra-fine Al powder with a particle size of 2 µm and three layers of medium Al powder with a particle size of 50 µm were alternately stacked through a screen. The powders were compacted, and the Al-Zr rolled sample plate was placed in the mold for bonding. Then, three layers of ultra-fine Al powder with a particle size of 1 µm and three layers of medium Al powder with a particle size of 40 µm were alternately stacked through a screen. m medium Al powder, compact the powder and remove the mold, then place the upper Al-Si-Mg rolled sample plate on the compacted Al powder for bonding, the total thickness of the stacked powder after piling and compaction is 400µm, and then preheat it at 545℃ for 1min, then perform alternating hot rolling and cold rolling cumulative rolling welding, the total rolling reduction is 90%, and perform 6 rolling, the first pass of cumulative rolling has a hot rolling reduction of 60%, and then immediately liquid nitrogen cooling for 10h, and immediately perform the second pass of cold rolling after taking out, with a reduction of 30%, to form an aluminum alloy composite plate with Al-Si-Mg / Al-Zr / Al-Si-Mg structure.
[0030] Example 4 The elements in the aluminum alloy composite plate are Si 4.2%, Mg 0.2%, Zr 0.2%, and the rest is Al, in terms of mass percentage.
[0031] The method for preparing an aluminum alloy composite plate comprises the following steps: (1) Calculating the required amounts of Si, Mg and Zr in proportion, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 760°C to melt, adding pure Si and pure Mg in turn, stirring and melting at 760°C, and then keeping it at 760°C for 30 minutes to prepare an Al-Si-Mg alloy melt, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 760°C to melt, adding an Al-Zr intermediate alloy, stirring and melting at 760°C, and then keeping it at 760°C for 40 minutes to prepare an Al-Zr alloy melt, and then sending them into a mold at 230°C for casting to obtain an Al-Si-Mg ingot and an Al-Zr ingot; (2) The Al-Si-Mg ingot and the Al-Zr ingot were homogenized at 520°C for 2 h, furnace cooled for 24 h and then air cooled, then solution treated at 530°C for 1 h, and then aged at 240°C for 15.9 h to obtain Al-Si-Mg alloy specimens and Al-Zr alloy specimens. The Al-Si-Mg alloy specimens and the Al-Zr alloy specimens were cut to a width ratio of 5:3, a length ratio and a thickness ratio of 1:1.2, and then placed in liquid nitrogen for deep cryogenic treatment for 8 h and then cold rolled. The cold rolling reduction was 95% and the rolling passes were 6 times to obtain Al-Si-Mg rolled specimen plates and Al-Zr rolled specimen plates. The thickness of the Al-Si-Mg rolled specimen plates and the Al-Zr rolled specimen plates were both 1.5 mm. (3) The Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate were pre-treated by removing edge cracks, surface cleaning, polishing and grinding. Then, the Al-Zr rolled sample plate was placed between the two Al-Si-Mg rolled sample plates. A mold that matched the size of the Al-Zr rolled sample plate was placed on the lower Al-Si-Mg rolled sample plate, and three layers of ultra-fine Al powder with a particle size of 2 µm and three layers of medium Al powder with a particle size of 60 µm were alternately stacked through a screen. The powders were compacted, and the Al-Zr rolled sample plate was placed in the mold for bonding. Then, three layers of ultra-fine Al powder with a particle size of 1 µm and three layers of medium Al powder with a particle size of 40 µm medium Al powder is compacted and removed from the mold, and then the upper Al-Si-Mg rolled sample plate is placed on the compacted Al powder for bonding. The total thickness of the stacked powder after piling and compaction is 300µm. It is preheated at 550℃ for 2min, and then hot rolling and cold rolling are alternately cumulatively welded. The total rolling reduction is 50%, and the rolling is repeated 5 times. The first hot rolling reduction of the cumulative rolling is 40%, and then it is immediately cooled with liquid nitrogen for 10h. After being taken out, the second cold rolling is immediately performed with a reduction of 1% to form an aluminum alloy composite plate with Al-Si-Mg / Al-Zr / Al-Si-Mg structure.
[0032] Comparative Example 1 The element composition of the prepared composite plate is Si 4.0%, Mg 0.4%, and the rest is Al.
[0033] (1) Calculate the required amounts of Si and Mg according to the ratio, place the prepared pure Al in a graphite crucible of a crucible resistance furnace, heat it to 760°C for melting, add pure Si and pure Mg in turn, stir and melt at 760°C, keep the mixture at 760°C for 40 min to prepare an Al-Si-Mg alloy melt, and then cast it into a mold at 220°C to obtain an Al-Si-Mg ingot; (2) The Al-Si-Mg ingot was homogenized at 520°C for 2 h, furnace cooled for 24 h and then air cooled, then solution treated at 530°C for 1 h, and then aged at 240°C for 15 h to obtain Al-Si-Mg alloy samples. The Al-Si-Mg alloy samples were cut to a width ratio of 6:5, a length ratio and a thickness ratio of 1:1, and then placed in liquid nitrogen for deep cryogenic treatment for 8 h and then cold rolled. The cold rolling reduction was 90% and the rolling passes were 7 times to obtain Al-Si-Mg rolled sample plates. The thickness of the Al-Si-Mg rolled sample plates was 1.5 mm. (3) The Al-Si-Mg rolled sample plate is pre-treated by removing edge cracks, cleaning the surface, polishing, and grinding. Then, the three layers of Al-Si-Mg rolled sample plates are bonded together. A mold that matches the size of the middle layer Al-Si-Mg rolled sample plate is placed on the lower layer Al-Si-Mg rolled sample plate, and three layers of ultra-fine Al powder with a particle size of 1 µm and three layers of medium Al powder with a particle size of 40 µm are alternately stacked through a screen. The powder is compacted, and the middle layer Al-Si-Mg rolled sample plate is placed in the mold for bonding. Then, three layers of ultra-fine Al powder with a particle size of 1 µm and three layers of medium Al powder with a particle size of 40 µm are alternately stacked through a screen. The powder is a medium Al powder of 40µm. The powder is compacted and the mold is removed. Then the upper Al-Si-Mg rolled sample plate is placed on the compacted Al powder for bonding. The total thickness of the stacked powder after stacking and compaction is 200µm. Then it is preheated at 550℃ for 2min. Then, hot rolling and cold rolling are alternately performed for cumulative rolling and welding. The total rolling reduction is 50%. The rolling is repeated 5 times. The first hot rolling reduction of the cumulative rolling is 25%, and then it is immediately cooled with liquid nitrogen for 6h. After being taken out, the second cold rolling is immediately performed with a reduction of 25% to form a composite plate with Al-Si-Mg structure.
[0034] Comparative Example 2 The element composition of the prepared composite plate is Si 4.0%, Mg 0.4%, Zr 0.5%, and the rest is Al.
[0035] (1) Calculating the required amounts of Si, Mg and Zr in proportion, placing the prepared pure Al in a graphite crucible of a crucible resistance furnace, heating it to 760°C for melting, adding pure Si, pure Mg and Al-Zr master alloy in turn, stirring and melting at 760°C, and then keeping the mixture at 760°C for 40 min to prepare an Al-Si-Mg-Zr alloy melt, which was then cast into a mold at 220°C to obtain an Al-Si-Mg-Zr ingot; (2) The Al-Si-Mg-Zr ingot was homogenized at 520°C for 2 h, furnace cooled for 24 h and then air cooled, then solution treated at 530°C for 1 h, and then aged at 240°C for 15 h to obtain Al-Si-Mg-Zr alloy samples. The Al-Si-Mg-Zr alloy samples were cut to a width ratio of 6:5, a length ratio and a thickness ratio of 1:1, and then placed in liquid nitrogen for deep cryogenic treatment for 8 h and then cold rolled. The cold rolling reduction was 90% and the rolling passes were 7 times to obtain Al-Si-Mg-Zr rolled sample plates. The thickness of the Al-Si-Mg-Zr rolled sample plates was 1.5 mm. (3) The Al-Si-Mg-Zr rolled sample plate is pre-treated by removing edge cracks, cleaning the surface, polishing and grinding, and then the three layers of Al-Si-Mg-Zr rolled sample plates are bonded together. A mold that matches the size of the middle layer Al-Si-Mg-Zr rolled sample plate is placed on the lower layer Al-Si-Mg-Zr rolled sample plate, and three layers of ultra-fine Al powder with a particle size of 1 µm and three layers of medium Al powder with a particle size of 40 µm are alternately stacked through a screen. The powders are compacted, and the middle layer Al-Si-Mg-Zr rolled sample plate is placed in the mold for bonding, and then three layers of ultra-fine Al powder with a particle size of 1 µm and three layers of medium Al powder with a particle size of 40 µm are alternately stacked through a screen. Three layers of medium Al powder with a particle size of 40µm are prepared. The powder is compacted and the mold is removed. Then the upper layer of Al-Si-Mg-Zr rolled sample plate is placed on the compacted Al powder for bonding. The total thickness of the stacked powder after stacking and compaction is 200µm. It is then preheated at 550℃ for 2min. Then, alternating hot rolling and cold rolling are performed for cumulative rolling welding. The total rolling reduction is 50%. The rolling is repeated 5 times. The first hot rolling reduction of the cumulative rolling is 25%, and then it is immediately cooled with liquid nitrogen for 6h. After being taken out, the second cold rolling is immediately performed with a reduction of 25% to form a composite plate with Al-Si-Mg-Zr structure.
[0036] Comparative Example 3 In step (2), no solution treatment and aging treatment are performed, and the remaining operations are the same as in Example 1.
[0037] Comparative Example 4 In step (3), powder stacking is not performed, and the remaining operations are the same as those in Example 1.
[0038] Comparative Example 5 In step (3), the powder is stacked by stacking 6 layers of ultra-fine Al powder with a particle size of 1 μm in the interlayer, and the remaining operations are the same as in Example 1.
[0039] Comparative Example 6 In step (3), the powder is stacked by stacking 6 layers of medium Al powder with a particle size of 40 μm in the interlayer, and the remaining operations are the same as in Example 1.
[0040] The performance tests were performed on the aluminum alloy composite plates prepared in Examples 1-4 and Comparative Examples 1-6, wherein: (1) The reference standard for room temperature ultimate tensile strength and elongation is the National Standard of the People's Republic of China "Room Temperature Tensile Test Method for Metallic Materials" (GB / T 228.1-2010); (2) Thermal conductivity measurement complies with the international standard ISO 18566-2010 "Thermal conductivity measurement method"; (3) The microhardness test was performed using a Vickers hardness tester, and the average value was taken from 15 points of each sample. (4)
[0042] From Table 1 in combination with Examples 1-4 and Comparative Examples 1-6, it can be seen that the present invention uses two types of rolled sample plates to roll into aluminum alloy composite plates, which can not only achieve grain refinement, but also improve material strength and plasticity at the same time. Although Comparative Examples 1-2 have higher tensile strength and Vickers hardness, their elongation is poorer than that of Example 1 and cannot meet the characteristics of high strength and toughness. Moreover, the different grain sizes and widths of plates produced during rolling of plates of different alloy materials can assist in the accumulation of the bonding of the plates during rolling folding. The powder stacking and hot rolling combination before rolling folding are conducive to the close bonding of the interface. The resulting bimodal structure of fibrous coarse grains and ultrafine grains can further improve the strength and toughness of the material. The alternating combination of hot and cold rolling during rolling folding further refines the grains and second phase size of the plate. The combination of dissimilar materials achieves complementary properties and has a more obvious advantage of high alloy element addition compared to rolling folding of the same material. The gradient-layered-bimodal Al-Si-Mg / Al-Zr / Al-Si-Mg composite structure obtained by rolling folding has better comprehensive mechanical properties, with a tensile strength ≥335MPa, an elongation ≥24%, and a hardness ≥88HV.
Claims
1. A method for preparing an aluminum alloy composite plate, characterized in that: The following steps are involved: (1) Pure Al, pure Si and pure Mg are stirred and melted, and then kept warm and allowed to stand to prepare an Al-Si-Mg alloy melt; pure Al and Al-Zr master alloy are stirred and melted, and then kept warm and allowed to stand to prepare an Al-Zr alloy melt, and then cast to obtain Al-Si-Mg ingots and Al-Zr ingots respectively; (2) The Al-Si-Mg ingot and the Al-Zr ingot are homogenized, and then subjected to solution treatment and aging treatment to obtain Al-Si-Mg alloy specimens and Al-Zr alloy specimens, and the Al-Si-Mg alloy specimens and the Al-Zr alloy specimens are cut, and then subjected to cryogenic treatment and cold rolling to obtain Al-Si-Mg rolled specimen plates and Al-Zr rolled specimen plates; (3) The Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate are pretreated, powder stacking is performed between the layers of the pretreated Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate, and then bonding, preheating and cumulative lamination welding are performed to obtain an aluminum alloy composite plate.
2. The method for preparing the aluminum alloy composite plate according to claim 1, characterized in that: In step (1), the smelting temperature is 750-790°C, the casting temperature is 220-250°C, the insulation temperature is 750-790°C, and the insulation time is 20-40 minutes.
3. The method for preparing the aluminum alloy composite plate according to claim 1, characterized in that: In step (2), the temperature of the homogenization treatment is 515-525°C, the time of the homogenization treatment is 1.9-2.1h, the temperature of the solution treatment is 525-535°C, the time of the solution treatment is 0.9-1.1h; the temperature of the aging treatment is 238-242°C, the time of the aging treatment is 15.8-16.2h.
4. The method for preparing the aluminum alloy composite plate according to claim 1, characterized in that: In step (2), the Al-Si-Mg alloy sample and the Al-Zr alloy sample are cut to a width ratio of 5-8:3-6, a length ratio of 1:1-1.5, and a thickness ratio of 1:1-1.
5.
5. The method for preparing the aluminum alloy composite plate according to claim 1, characterized in that: In step (2), the medium for cryogenic treatment is liquid nitrogen, the time for cryogenic treatment is 4-10 hours, the reduction of cold rolling is 84-95%, the number of cold rolling passes is 5-8 times, and the thickness of the Al-Si-Mg rolled sample plate and the Al-Zr rolled sample plate are both 1.3-1.7 mm.
6. The method for preparing the aluminum alloy composite plate according to claim 1, characterized in that: In step (3), the mass percentages of the elements in the aluminum alloy composite plate are Si: 4.0-5.0%, Mg: 0.2-0.8%, Zr: 0.2-1.0%, and the rest is Al.
7. The method for preparing the aluminum alloy composite plate according to claim 1, characterized in that: The pretreatment in step (3) includes removing edge cracks, surface cleaning, polishing and grinding.
8. The method for preparing the aluminum alloy composite plate according to claim 1, characterized in that: In step (3), the powder stacking is to alternately and evenly stack the ultrafine Al powder with a particle size of 1-2µm and the medium Al powder with a particle size of 40-60µm between the layers of adjacent Al-Si-Mg rolled sample plates and Al-Zr rolled sample plates and compact them. The total thickness of the stacked powder after stacking and compaction is 200-500µm. The bonding is to place the Al-Zr rolled sample plate between two layers of Al-Si-Mg rolled sample plates. The preheating temperature is 545-555°C and the preheating time is 1-2min.
9. The method for preparing the aluminum alloy composite plate according to claim 1, characterized in that: In step (3), the cumulative roll-to-roll welding is performed by alternating hot rolling and cold rolling, the total reduction of the roll-to-roll is 50-90%, and the number of roll-to-roll is 3-6 times.
10. The method for preparing the aluminum alloy composite plate according to claim 9, characterized in that: The rolling process is performed twice, the first one is hot rolling and the second one is cold rolling. The hot rolling is followed by liquid nitrogen cooling for 4-10 hours and cold rolling is performed immediately after the hot rolling.
Citation Information
Patent Citations
Aluminum / magnesium / aluminum alloy composite material and preparation process thereof
CN113290048A
Preparation method of metal magnesium-copper-graphene layered composite material
CN114000182A
Composite forming method of aluminum alloy with coarse grain-fine grain layered distribution structure
CN117444536A
Preparation method of zinc oxide particle strengthened aluminum-based composite
CN106270509A
Preparation method of aluminum-magnesium-aluminum layered heterogeneous alloy plate
CN111375773A
Cited By
Preparation method of heterogeneous aluminum alloy composite board
CN121423372A